TEAM QUIZ LEARNING MODEL: IMPROVING ELEMENTARY SCHOOL STUDENTS' MATHEMATICAL COGNITIVE LEARNING OUTCOMES - Johannis Takaria; La Suha Ishabu; Samsudin Soumena (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to examine the effect of the Team Quiz learning model on improving fourth-grade students’ mathematical cognitive learning outcomes in flat shape material at SD Inpres 55 Ambon. Using a quasi-experimental one-group pretest-posttest design, data were analyzed through the Wilcoxon non-parametric test due to non-normal and non-homogeneous distributions. The results yielded a significance value of 0.000 < 0.05, indicating a significant difference before and after the implementation. N-Gain analysis showed high improvement for 2 students (0.71), moderate for 16 students (0.42), and low for 3 students (0.25). These findings confirm that the Team Quiz model effectively enhances mathematical cognitive outcomes. The novelty of this study lies in integrating a competitive and collaborative learning approach to strengthen student engagement and motivation. The results contribute to evidence-based innovations in mathematics education, emphasizing active learning strategies that foster deeper understanding and improved academic performance.